(3GdHjGf hGdJMUjd aj eSGFd GdeSJNQLIs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s; (3CMeO Hf eMeO HGeaJM Hf GdYQHj GdUbdjs
(3ChdgG (B:s
(3hef cJGH Chdg HGY TGg hGSJKfi LdOgG s
(3BNQgG (B:s
(3jfJgi CKfGA hef cJGH Chdg GZJSd Ydi ZjQ fjI s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(75) s
Keywords: (3Gdabg GdeGdcjs